The Impact of Faith-Based Organizations on Da’wah and Community Development in Kano State, Nigeria - Abubakar Sani; Bilyaminu Muhammad (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
The propagation of Islam and community development is inseparable in the message of Islam. Da’wah as the first method used by all the Prophets/Messengers of Allah (SWT) to deliver the task of salvaging the Ummah from wrong direction to the path of peace and success. With da’wah a lot have been achieved in the history of Islam which continued to exist up to the present time. These giant efforts have continued to yield tremendous transformation in the number of Muslims and welfare services which Muslim organizations established. Kano State is one of the areas that attracted many migrant Scholars (Ulama’) to propagate Islam which led to the emergence of many Islamic non-governmental organizations (INGOs). Before Islam and the activities of these Organizations people in some parts of Kano worshiped at Tsumburbura and other pagan shrines and a lot of offerings took place; to the extent that the welfare and development of the Ummah was neglected. This paper adopts qualitative method and discovered that, these organizations have been transforming the lives of people in the state not only in da’wah but also through many community services such as Mosques, Islamic schools, Mobile healthcare, accommodations for revertees, Ramadan welfare among others. However, some of these programmes are not properly documented and presented due to administrative lapses and lack of good accountability that will attract more supports/funds everywhere that would enhance their activities. It recommends massive awareness for more community services from these organizations, training and re-training for all the executives and patrons of these groups and good record keeping..